An address to the working-men of New-England, on the state of education, and on the condition of the producing classes in Europe and America. With particular reference to the effect of manufaturing (as now conducted,) on the health and happiness of the poor, and on the safety of our republic. Delivered in Boston, Charlestown, Cambridgeport, Waltham, Dorchester, Mass., Portland, Saco, Me., and Dover, N.H (Publ. by the Author, 1832)
Entered according to act of Congress, in the year 1832.